The Influence of the Mayor of Lubuklinggau's Personal Branding on Community Satisfaction - Rizqi, Muhammad Dimas; Tiansah, Agus; Lestari, Umi Fitriana; Murahman, Mardi (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2025)
The aim of this study is to see how personal branding or Prana Putra Sohe through Instagram @Prana_Putra_Sohe as town major of Lubuklinggau increasing local people satisfaction. This is quantitative study through questionnaire, observation and documentation. Population of this study is taken from the 51.300 followers of town major Instagram of Lubuklinggau namely @Prana_Putra_Sohe in march of 2023. The sample is taken by using random sampling and Taro Yamane formula such of 100 samples. Analyzing data of this study validity, realibility, simple linear regression, T test and determinant cooficient test (R2). The data is analyzed by using SPSS program version 26. The result of cooficient determination is 0,564 as percentage of 56,4 percent by means the variable of society satisfaction is affected by Personal Branding with 56,4 percent. T test result namely T count 11,268 is bigher than T table with 9,237 and significance value of 0,000 by means H1 is accepted and H0 is rejected. The result of T test proses the hypothesis namely â€œThereâ€™s a significance effect between Personal Branding toward local people satisfaction in Instagram of town major of Lubuklinggau which is proven trueâ€.